Tun Dr. Ismail : merintis kepemimpinan berintegriti - Khairul Azman Suhaimy; Hussain Othman; Mustaffa Ibrahim (Batu Pahat : Penerbit Universiti Tun Hussein Malaysia, 2012)
Biography of Tun Ismail, a politician and deputy prime minister of Malaysia from 1970 to 1973.
Mengandungi indeks.
Bibliografi : mukasurat 137-142.
Keywords: Ismail, -- Tun, -- 1915-1973.; Politicians -- Malaysia -- Biography; Cabinet officers -- Malaysia -- Biography; Malaysia -- Politics and government -- 20th century